### Telescoping series

Most series are neither arithmetic nor geometric. Some of these series can be summed by expressing the summand as a difference.

#### Example

1. Find the sum $\sum_{k=2}^n \dfrac{2}{k^2-1}.$
2. Does the infinite series $\sum_{k=2}^\infty \dfrac{2}{k^2-1}$ have a limiting sum? If so, what is its value?

#### Solution

1. We can factor $$k^2-1$$ and split the summand into $\dfrac{2}{k^2-1} = \dfrac{1}{k-1} - \dfrac{1}{k+1}.$

Thus,

\begin{align*} \sum_{k=2}^n \dfrac{2}{k^2-1} &= \sum_{k=2}^n \Bigl( \dfrac{1}{k-1} - \dfrac{1}{k+1} \Bigr) \\ &= \sum_{k=2}^n \dfrac{1}{k-1} - \sum_{k=2}^n \dfrac{1}{k+1}. \end{align*} If we write out the terms of these two sums, we have $\Bigl(1 + \dfrac{1}{2} + \dfrac{1}{3} + \dfrac{1}{4} + \dots + \dfrac{1}{n-2} + \dfrac{1}{n-1} \Bigr) - \Bigl(\dfrac{1}{3} + \dfrac{1}{4} + \dots + \dfrac{1}{n-2} + \dfrac{1}{n-1} + \dfrac{1}{n} + \dfrac{1}{n+1}\Bigr).$ Most of the terms cancel out (telescope), giving \begin{align*} \sum_{k=2}^n \dfrac{2}{k^2-1} &= 1 + \dfrac{1}{2} - \dfrac{1}{n} - \dfrac{1}{n+1} \\ &= \dfrac{3}{2} - \dfrac{1}{n} - \dfrac{1}{n+1}. \end{align*}
2. Since the terms $$\dfrac{1}{n}$$ and $$\dfrac{1}{n+1}$$ go to zero as $$n$$ goes to infinity, the series has a limiting sum of $$\dfrac{3}{2}$$.

Next page - Links forward - The harmonic series